2000
DOI: 10.1016/s1010-7940(00)00518-2
|View full text |Cite
|
Sign up to set email alerts
|

Does aprotinin reduce lung reperfusion damage after cardiopulmonary bypass?✩

Abstract: Results represented in our study indicate that addition of aprotinin (2 million units) into the prime solution during CPB can reduce lung reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Aprotinin, a nonspecific serine protease inhibitor, has been extensively used in cardiac operations to reduce postoperative blood loss [4,[8][9][10][11][12]. In a recent report, neutrophil extravasation in association with ROS production, a necessary step in the inflammatory cascade, was inhibited by aprotinin in the mesenteric microcirculation [8], or during cardiopulmonary bypass [9].…”
Section: Introductionmentioning
confidence: 99%
“…Aprotinin, a nonspecific serine protease inhibitor, has been extensively used in cardiac operations to reduce postoperative blood loss [4,[8][9][10][11][12]. In a recent report, neutrophil extravasation in association with ROS production, a necessary step in the inflammatory cascade, was inhibited by aprotinin in the mesenteric microcirculation [8], or during cardiopulmonary bypass [9].…”
Section: Introductionmentioning
confidence: 99%
“…7,23,24 In the control group, there was a statistically very significant (p<0.001) increase in the levels of MDA in the postoperative period but in the study group there was a decrease in the postoperative period, and was not statistically significant (p=0.569). Thus in the postoperative period, the MDA levels were significantly higher in the control group (p=0.033), implying an attenuated oxidative injury in the NAC treated group.…”
Section: Discussionmentioning
confidence: 89%
“…27 To counterbalance this sequence of events and diminish oxidative injury, several studies have investigated and recommended the use of antioxidant supplements, 8,9 viz. Steroids, 28 aprotinin, 23 pentoxiphylline, 29 N-acetylcysteine.…”
Section: Discussionmentioning
confidence: 99%
“…It is presently widely used for minimizing perioperative blood loss in cardiac operations [16]. Experimental studies have shown that aprotinin, beyond its antiproteolytic membrane stabilizing property, decreases the release of lysosomal enzymes and increases intracellular adenine nucleotides [17, 18]. Bradykinin, kallidin and other kinins (known inflammatory mediators) have a high activity as permeability factors.…”
Section: Introductionmentioning
confidence: 99%
“…Bradykinin, kallidin and other kinins (known inflammatory mediators) have a high activity as permeability factors. While aprotinin inhibits bradykinin, it can also inhibit the production of superoxides and peroxides which are originated from human PMNLs [17]. …”
Section: Introductionmentioning
confidence: 99%